2018
DOI: 10.1017/s0144686x18001241
|View full text |Cite
|
Sign up to set email alerts
|

Care and the shadow of the fourth age: how does home care get caught up in it and how does it stay away from it?

Abstract: This article examines how care encounters at the elders’ homes are forged, and how the way these encounters are forged avoids or evokes the social imaginary of the fourth age. Data were gathered in Portugal from elders receiving home care (16 cases), their care workers (eight cases) and family carers (six cases), through participant observation and informal conversations (conducted at the elders’ homes), as well as focus groups. The collected data were analysed according to the procedures of Framework Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…This care provider role was dynamically evolving, through provider and manager, into a single care manager modality, which was considered to continue post-transition. This is aligned to the emerging understanding of the complexity consistent within the caring role (Ryan and McKenna, 2015; São José, 2018). This change in the care-giving role was a natural transition that emerged from the need to support their loved one move into TESA and emerged from the ‘hitting the crisis point’ theme where ICs identified the provision of safety as a key issue.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This care provider role was dynamically evolving, through provider and manager, into a single care manager modality, which was considered to continue post-transition. This is aligned to the emerging understanding of the complexity consistent within the caring role (Ryan and McKenna, 2015; São José, 2018). This change in the care-giving role was a natural transition that emerged from the need to support their loved one move into TESA and emerged from the ‘hitting the crisis point’ theme where ICs identified the provision of safety as a key issue.…”
Section: Discussionmentioning
confidence: 62%
“…Informal care-giving will generally have a relational dimension, and whilst often the spouse is the main carer, other family members often provide a significant contribution (McDonnell and Ryan, 2014). There are many stages to caring and indeed the nature and type of care varies depending on the needs of the person receiving the care (São José, 2018). Many studies have reported the negative impact of care-giving, particularly on those who care for people living with dementia who may experience clinical depression or anxiety or other less-severe psychological impacts (Cross et al, 2018; Ryan et al, 2018; Wang et al, 2018; Watson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBCD often focuses on specific aspects or moments in service delivery that impact the experiences of service users. However, in long‐term care, the care relationship is central to the quality of care 7–10 . The focus of EBCD in these settings should thus be on the care relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, in long‐term care, the care relationship is central to the quality of care. 7 , 8 , 9 , 10 The focus of EBCD in these settings should thus be on the care relationship. This care relationship is complex as it is often laden with value tensions.…”
Section: Introductionmentioning
confidence: 99%